If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -8x = 58 + -43x Solving 8 + -8x = 58 + -43x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '43x' to each side of the equation. 8 + -8x + 43x = 58 + -43x + 43x Combine like terms: -8x + 43x = 35x 8 + 35x = 58 + -43x + 43x Combine like terms: -43x + 43x = 0 8 + 35x = 58 + 0 8 + 35x = 58 Add '-8' to each side of the equation. 8 + -8 + 35x = 58 + -8 Combine like terms: 8 + -8 = 0 0 + 35x = 58 + -8 35x = 58 + -8 Combine like terms: 58 + -8 = 50 35x = 50 Divide each side by '35'. x = 1.428571429 Simplifying x = 1.428571429
| (2x+3)-1=6 | | 4x-39=647 | | y=4E+07 | | x+38+4x-39=857 | | 3x^2=-4x-1 | | 2v=8 | | 4x^2-144= | | 2x+11x=65+x | | 6x^2-54= | | 25x^2+10x+1= | | 84-3x=15x+16 | | 11-9x=51-44x | | 7x^2-7x-210= | | 15v^2+34v-16=0 | | 4n^5+3.5n^5+(-2.1n^5)= | | 7y^3-20y^2-3y=0 | | 2(3c-1)-4=4c+4 | | 7x+(-.75)=8 | | 15x^2-25x-60= | | 5x+-x-(x+5)=1 | | 15x^2-25-60= | | 14x-(3x+2)-10=10x-1 | | 25x^2-95x-20= | | 18h^2-42h=0 | | 18x^2+42= | | 12x^2+30= | | x+y+z=4 | | 5x^2=2x+6 | | x-(5x+1)=-3x+(-x+2) | | -x^2+x-20= | | -x^2-7x-18= | | (5-3x)-(-4x+6)=5x+17 |